In Vitro Collapsing Colon Cancer Cells by Selectivity of Disulfiram-Loaded Charge Switchable Nanoparticles Against Cancer Stem Cells - M. Abu-Serie, Marwa; H. El-Rashidy, Fatma (Recent Patents on Anti-Cancer Drug Discovery, 2017)
Background: Different strategies against colon cancer are accompanied by treatment failure, because of drug toxicity toward normal cells and cancer stem cells (CSCs) resistance. However, previous patent evaluated liposome that encapsulated inhibitor of CSCs' aldehyde dehydrogenase (ALDH)1; disulfiram, for targeting breast CSCs. Liposome has disadvantages due to its hydrophobicity. Objectives: Designing hydrophilic nanoparticles has selectivity to release disulfiram in CC cells rather than in normal colonocytes based on variation in microenvironment between normal and cancer cells. Methods: Disulfiram was nanoformulated by its loading into cationic chitosan and coating with anionic albumin. Their selectivity and targeting were investigated using murine and human colon cancer cells compared to normal mice colon cells. Results: Zeta potential of the coated nanoparticles confirmed that albumin-layering confers negative charge (-10.3mv) for disulfiram-loaded chitosan nanoparticles (52.9mv). In slightly acidic medium of tumor, the ionic bond between albumin and chitosan hydrolyzed then the positive charge was reversed (47.6mv). Thus coated nanoparticles showed higher sustain release for disulfiram in tumor microenvironment than neutral pH and their uptake was higher in cancer cells than normal cells. This interpreted the highest selectivity of coated nanoparticles for enhancing apoptosis and eliminating CSCs in cancer cells. Conclusion: These patented coated nanoparticles were the most effective and selective for eradicating colon CSCs without insulting normal stem cells in comparison with disulfiram which was toxic to both normal and CSCs. This novel study that used charge switchable (hydrophilic) nanoparticles for targeting colon CSCs may represent a basis for future in vivo studies.
Keywords: Apoptosis